Recognition of a Clickable Abasic Site Analog by DNA Polymerases and DNA Repair Enzymes - Endutkin, Anton V.; Yudkina, Anna V.; Zharkov, Timofey D.; Kim, Daria V.; Zharkov, Dmitry O. (International journal of molecular sciences, 2022)
Azide–alkyne cycloaddition (“click chemistry”) has found wide use in the analysis of molecular interactions in living cells. 5-ethynyl-2-(hydroxymethyl)tetrahydrofuran-3-ol (EAP) is a recently developed apurinic/apyrimidinic (AP) site analog functionalized with an ethynyl moiety, which can be introduced into cells in DNA constructs to perform labeling or cross-linking in situ. However, as a non-natural nucleoside, EAP could be subject to removal by DNA repair and misreading by DNA polymerases. Here, we investigate the interaction of this clickable AP site analog with DNA polymerases and base excision repair enzymes. Similarly to the natural AP site, EAP was non-instructive and followed the “A-rule”, directing residual but easily detectable incorporation of dAMP by E. coli DNA polymerase I Klenow fragment, bacteriophage RB69 DNA polymerase and human DNA polymerase β. On the contrary, EAP was blocking for DNA polymerases κ and λ. EAP was an excellent substrate for the major human AP endonuclease APEX1 and E. coli AP exonucleases Xth and Nfo but was resistant to the AP lyase activity of DNA glycosylases. Overall, our data indicate that EAP, once within a cell, would represent a replication block and would be removed through an AP endonuclease-initiated long-patch base excision repair pathway.